SOSIALISASI ALAT INSTALASI PENGASAPAN DAN DIGITALISASI MARKETING OLEH KELOMPOK USAHA IKAN ASAP TRADISIONAL DI DESA BINTANG MERIAH - Khairiah, Khairiah; Shuharianto, Joko; Harahap, Ardhansyah Putra (LPPI UMN AL WASHLIYAH, 2024)
This community service activity's primary goal is to address the production and marketing-related issues that partners are facing. The production aspect can be resolved by developing the vacuum seal tool for fish packaging and the smoking installation tool known as smart strongbox smoked; the digital marketing aspect can be resolved by coming up with a company name, trademark stickers, and an online store account management system. Observation, focus group discussions (FGD) to identify issues and potential solutions, production tool design, product sales packaging design training, and online store account creation are the approaches taken in this activity. The following are the outcomes/results of this activity: a) the existence of a vacuum seal tool and smart strongbox smoked; b) the existence of an online store account and business brand for Sayur Matinggi smoked catfish products; c) the existence of a more appealing product sales packaging design; and d) the transfer of tools and materials to support the growth of partners' businesses. It was determined that the traditional smoked fish group had gained more knowledge as a result of this socializing exercise, indicating its success.